Explore the changes of metabolites in feces and serum of acute pancreatitis patients with different etiologies by LC-MS based metabolomics strategy - Cui, Meng-Yan; Fan, Miao-Yan; Wu, Jun; Chen, Su-Min; Zhao, Meng-Qi; Jiang, Qiao-Li; Wang, Jing-Jing; Zeng, Yue; Zhao, Yu; Lu, Ying-Ying (Frontiers in Pharmacology, 2025)
BackgroundAcute pancreatitis (AP) is a common abdominal inflammatory disease, which is mainly caused by gallstones, hyperlipidemia, and so on. Previous studies have explored the changes of serum metabolites in patients with AP. However, whether different etiologies have distinct impacts on the fecal and serum metabolites of the AP patients is still in suspense.AimThis investigation was designed with dual objectives: (1) to systematically delineate etiology-specific alterations in metabolic profiles and associated pathway perturbations in AP cohorts, and (2) to evaluate their potential as diagnostic biomarkers and pathogenesis-targeted therapeutic strategies.MethodsFifteen stool samples and fifteen serum samples from the patients with biliary acute pancreatitis (BAP) and hyperlipidemic acute pancreatitis (HAP), respectively, were analyzed. Metabolites were quantified by using ultrahigh performance liquid chromatography-mass spectrometry (UPLC-MS). The anti-inflammatory properties of Gibberellin A4 (GA4) and catechin were verified by RT-qPCR in vitro.ResultsThe metabolites in feces and serum of the AP group were significantly different from that of the control group. Compared with the control group, a total of 10 fecal metabolites were significantly altered in the AP group. In the serum metabolites, five differential metabolites were identified between the AP and control groups. Receiver operating characteristic analysis of the subjects found that important differential metabolites can distinguish AP patients with different etiology from healthy people, and in vitro experiments found that GA4 and catechin could reduce the expression of inflammatory factors in pancreatic 266-6 cell line.ConclusionThe significant differential metabolites between AP patients and healthy people can clearly distinguish the two groups, and GA4 and catechin have anti-inflammatory effects on pancreatic cell lines. The identification of distinct metabolites enabled to distinguish the AP patients with different etiologies.